Dynamic optimization method of secondary cooling water quantity in continuous casting based on three-dimensional transient nonlinear convective heat transfer equation - Yu, Yang; Luo, Xiaochuan; (Yulin) Zhang, Huaxi; Zhang, Qingxin (Applied thermal engineering, 2019)
•3-Dimensional transient nonlinear convective heat transfer equation is used.•A dynamic optimization method is developed for setting the value of water flow rate.•A modified adaptive step size quasi-Newton parallel iterative algorithm is presented.•Actual data in a steel plant are used to demonstrate the validity of optimization method. The defects of a slab, such as shrinkage and crack, are related to non-uniform cooling in secondary cooling zone (SCZ) of continuous casting, hence setting the value of water flow rate in the SCZ plays a vital role for the quality of slab. The traditional scheme can lead to the great fluctuation of temperature when the casting speed changes. Therefore, based on 3-dimensional transient nonlinear convective heat transfer equation of a slab, this paper develops a dynamic optimization method for setting the value of water flow rate. However, it is difficult to realize this method due to the following two causes. 1. It costs too much time to calculate the 3-dimensional transient nonlinear convective heat transfer equation. 2. It is not easy to select a suitable step size for the optimization algorithm. So this paper presents a modified adaptive step size quasi-Newton parallel iterative algorithm, which can not only reduce the computing time but also select a suitable step size. Actual data in a steel plant are used to demonstrate its validity, and the results clearly show that this scheme can greatly reduce the running time and give a more stable temperature distribution.